Foresight in the game as a determinant of the effectiveness of technical and tactical operations among experienced handball players - Lutkova N.V. ,; Makarov Yu.M. ,; Pakholkova N.V. ,; Zinoviev N.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study. The main objective of the work was to increase the effectiveness of the competitive activity of experienced handball players through the use of exercises aimed at developing the ability to anticipate game situations. Methods and structure of the study. To assess the effectiveness of technical and tactical techniques, the matches of the Russian Handball Championship among youth teams were studied. An analysis of 40 games of the strongest teams was carried out. In order to study the methods used by coaches in the training process, 25 handball coaches with at least 10 years of experience were interviewed. The level of handball players' readiness for competitions was assessed during pedagogical diagnostics using testing. The psychological test "A-5 – Five types of anticipation in athletes" made it possible to identify and evaluate five different types of anticipatory abilities in handball players. The experiment included specialized sets of exercises aimed at developing five types of anticipation: spatial, spatial-situational, situational, temporal-situational and temporal. The study involved 30 handball players aged 18-20 years, representing the Zenit-2 and SKIF-2 teams. Results and conclusions. The results of the study showed the expediency of using five separate blocks of exercises to form a game anticipation aimed at developing its various types. It was found that improving the formation of spatial, spatial-situational and situational anticipation has a positive effect on the effectiveness of game actions, both for the goalkeeper and the field players of the team. The field players of the experimental group showed an improvement in the quality of technical and tactical actions in four key indicators: the accuracy of shots, the number of assists, the number of blocks and interceptions.